2010
DOI: 10.4049/jimmunol.0903758
|View full text |Cite
|
Sign up to set email alerts
|

Soluble IL-7Rα (sCD127) Inhibits IL-7 Activity and Is Increased in HIV Infection

Abstract: Soluble CD127 (sCD127) appears to play an important role in the immunopathogenesis of several chronic infections, multiple sclerosis, and various cancers. The function of sCD127 and whether it influences IL-7 bioavailability or activity is unknown. In this study, we demonstrated that recombinant and native sources of sCD127 significantly inhibited IL-7–mediated STAT5 and Akt phosphorylation in CD8+ T cells. IL-7–mediated proliferation and Bcl-2 expression were similarly reduced by sCD127. In each case, native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
72
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 54 publications
10
72
5
Order By: Relevance
“…13 Recently, it was shown that the receptor affinity of the soluble form is comparable to that of the membrane-bound IL-7Ra 14 and that the soluble receptor can inhibit IL-7 signaling in CD8 T cells of HIV patients. 15 Therefore, we investigated whether our results are influenced by complexes between IL-7 and sIL-7Ra. First, we assessed whether the sIL-7Ra enzyme-linked immunosorbent assay (ELISA) is inhibited by IL-7 binding.…”
Section: Resultsmentioning
confidence: 98%
“…13 Recently, it was shown that the receptor affinity of the soluble form is comparable to that of the membrane-bound IL-7Ra 14 and that the soluble receptor can inhibit IL-7 signaling in CD8 T cells of HIV patients. 15 Therefore, we investigated whether our results are influenced by complexes between IL-7 and sIL-7Ra. First, we assessed whether the sIL-7Ra enzyme-linked immunosorbent assay (ELISA) is inhibited by IL-7 binding.…”
Section: Resultsmentioning
confidence: 98%
“…Another interpretation of the different findings in Caucasians and Africans could be that our initial findings in the Caucasian cohort may not have been related to levels of sIL-7Ra but could have been due to other SNPs in LD with rs6897932, which may have had an influence on CD4 T-cell recovery. This is of course possible but we believe this is less likely given the clear relationship in vitro between sIL-7Ra levels and IL-7 function in primary T-cells, 36,37 and that sIL-7Ra has a binding affinity similar to membrane-bound IL-7Ra on T-cells. 38 Finding the opposite association between genotype and phenotype in replicate genetic studies has been described previously as a 'flip-flop phenomenon,' 39 and is commonly reported in genetic association studies across different ethnic groups.…”
Section: Discussionmentioning
confidence: 98%
“…Increased sIL-7R in serum from individuals with human immunodeficiency virus infection may therefore neutralize IL-7-mediated effects on T cells. 21,22 The immune system creates diversity and responds to infection by various adaptive mechanisms, one of them being alternative splicing of cytokine gene products. 23 For instance, alternatively spliced IL-4, lacking exon 2, is produced in response to Mtb infection.…”
Section: Introductionmentioning
confidence: 99%